circZNF707 promoted glycolysis and tumor progression through miR-668-3p-PFKM axis in NSCLC - Wei Chen; Shuai Fang; Xianqiao Wu; Tianzheng Fang; Ziyuan Chen; Wenmin Su; Yuchao Zhu; Xiaodong Zhao; Chengwei Zhou (European Journal of Medical Research)
Abstract Background Circular RNA (circRNA) plays an important regulatory role in the development of human malignancies, but the potential mechanisms of circRNA in non-small cell lung cancer (NSCLC) remain largely unknown. Methods Microarray analysis was used to test for circRNAs differing in expression between NSCLC tumors and healthy adjacent tissues. Using qRT-PCR, the expression of circZNF707 was determined. Through a number of loss-of-function and gain-of-function investigations, the biological behavior of NSCLC cells was evaluated. Finally, tests using Western blotting, RIP, qRT-PCR, and luciferase reporter gene detection and rescue assays revealed the potential mechanism of circZNF707. Results Increased expression of circZNF707 was found in NSCLC tissues. Functionally, circZNF707 enhances proliferation, migration, invasion, and glycolysis of NSCLC cells. Mechanistically, circZNF707 can upregulate PFKM by acting as a sponge for miR-668-3p, thus contributing to the progression of NSCLC. Conclusions Through the circZNF707/miR-668-3p/PFKM axis, upregulation of circZNF707 promotes tumor development. CircZNF707 may provide new insights into the treatment and diagnosis of NSCLC.